The Role of Transport Infrastructures in determining Technical Efficiency in R&D activity of Italian regions. A double-bootstrapped DEA procedure - Claudia Capozza; Angela Stefania Bergantino; Angela De Carlo (European Regional Science Association (ERSA), 2013)
We measure technical efficiency in R&D of Italian regions with the aim of understanding whether the variation in transport infrastructure endowment across regions might be the cause of efficiency disparities. We use a semi-parametric method where in the first step we estimate bootstrapped efficiency scores through DEA. In the second step, efficiency scores are explained in a bootstrapped truncated regression using transport infrastructure variables as non-discretionary inputs. We find that well-developed transport infrastructures seriously improve R&D efficiency by facilitating connections and, thus, knowledge transfer.
Keywords: C14; R11; O32; 330; R&D investiments; efficiency; Three-step DEA